Neuropsychological care after out-of-hospital cardiac arrest – the CARE clinic model. (2019) - Mion, Marco; Magee, Neil; Watson, Noel; Davies, John; Islam, Shahed; Al-Janabi, Firas; Karamasis, Grigoris; Balasubramanian, Rajesh; Keeble, Thomas
No abstract available